Narrativas de vida de Antígona (Sófocles), Sor Juana e Olympe de Gouges: a Justiça no divã da Análise do Discurso - Adriana do Carmo Figueiredo (2020)
The proposal of this thesis presents narratives of life as a research object that marked the foundations of the origins of the Law, through female voices enunciating the primitive and foundational thought that involves the complexity of Human Rights. The corpus is composed of epistles, declarations, dialogues and enunciative scenes of three literary exponents, Antigone of Sophocles (442 BC), Sor Juana Ines de la Cruz (1648-1695) and Olympe de Gouges (1748-1793). The theoretical references of the research focus, especially, in the Machado's theoretical approaches ( 2009, 2011, 2012, 2013, 2014, 2015, 2016, 2017, 2018) about the récit de vie, in the Semiolinguistic Theory of Charaudeau (1983, 2001, 1992, 2012, 2013, 2014, 2015 [2005]), in the Theory of Communicative Action, according to Habermas (2014 [1962], 2010 [1971],1999 [1981], 1989 [1983], 1997 [1992], 2002 [1996]), and in some concepts that touch on the notions of pamphletary ethos, according to Amossy (2014), and the dimension of the hyper-announcer, as proposed by Maingueneau (2008). For the literature review of the sources of Law, the research sought to map the theme, as outlined by legal science theorists in dialogue with the philosophy of Michel Foucault (2002 [1969], 2004 [1970]). This cartography of the sources gave us an initial reflection on the notions of tradition, discontinuity and rupture. As a result of our research, we verified to what extent these voices that compose the aforementioned corpus can be understood as precursors of the valuation bases that would lead us to re-significate the sources of Law in its enunciative, historical and sociological dimensions, by feminine views.